Numerical experiments on plasma focus neon soft x-ray scaling - Lee, S.; Saw, S. H.; Lee, P.; Rawat, R. S. (IOP Publishing, 2009)
Numerical experiments are carried out systematically to determine the neon soft x-ray yield Ysxr for optimized neon plasma focus with storage energy E0 from 0.2 kJ to 1 MJ. The ratio c = b/a, of outer to inner electrode radii, and the operating voltage V0 are kept constant. E0 is varied by changing the capacitance C0. Parametric variation at each E0 follows the order operating pressure P0, anode length z0 and anode radius a until all realistic combinations of P0, z0 and a are investigated. At each E0, the optimum combination of P0, z0 and a is found that produces the biggest Ysxr . At low energies the soft x-ray yield scales as Ysxr ∼ E1.6 0 whilst towards 1MJ it becomes Ysxr ∼ E0.8 0 . The Ysxr scaling laws are found to be Ysxr ∼ I 3.2 peak (0.1–2.4 MA) and Ysxr ∼ I 3.6 pinch (0.07–1.3 MA) throughout the range investigated. When numerical experimental points with other c values and mixed parameters are included, there is evidence that the Ysxr versus Ipinch scaling is more robust and universal, remaining unchanged whilst the Ysxr versus Ipeak scaling changes slightly, with more scatter becoming evident.